Ecological impacts of QX oyster disease and its management strategies - Emma Mary Wilkie (2014)
As a consequence of rising global consumption of seafood and over-extraction of wild finand shell-fisheries, aquaculture is the fastest growing food production method in the world. Although in some instances aquaculture may benefit wild populations by deflecting harvest pressure away from these, in others it may have negative impacts as a consequence of facilitation of disease or biological invasion or where it results in genetic pollution of wild populations with selectively-bred genotypes. The oyster industry of New South Wales (NSW), Australia, is presently entirely dependent on aquaculture. Although the NSW industry historically cultured wild-caught native Sydney rock oysters (Saccostrea glomerata), in recent years high mortality of cultured oysters from QX disease has led to a shift towards culture of Sydney rock oysters selectively bred for disease resistance and non-native Pacific oysters (Crassostrea gigas) that are unaffected by the disease. It is unknown how QX disease or the resulting strategies of management that have been applied to the aquaculture industry (culture of disease resistant Sydney rock or Pacific oysters) may impact wild populations of Sydney rock oysters, and their important ecosystem services, which include provision of habitat and food for associated communities of fish and invertebrates. This thesis determined: (1) how QX disease has impacted wild populations of Sydney rock oysters, both directly and indirectly as a result of any facilitation of Pacific oysters, and (2) whether wild-stock Sydney rock oysters, disease resistant Sydney rock oysters, and Pacific oysters are functionally equivalent in their provision of habitat and food to associated communities of invertebrates. -- Sampling in the Hawkesbury River, NSW, where QX disease has produced aquaculture mortality of Sydney rock oysters of up to 90%, revealed only a low (<14%) prevalence of the disease-causing parasite among wild Sydney rock oysters on rocky shores. Consequently, mortality rates of wild Sydney rock oysters ...